Study of Metakaolinite Geopolymeric Mortar with Plastic Waste Replacing the Sand: Effects on the Mechanical Properties, Microstructure, and Efflorescence - Soares, Ivana [UNESP]; Nobre, Francisco X.; Vasconcelos, Raimundo; Ramírez, Miguel A. [UNESP] (MDPI, 2022)
In this study, the production of a mortar was proposed in which plastic waste replaced sand by 0%, 50%, and 100% in order to create a sustainable alternative for construction. The performance of the mortars was tested with two types of activators, one with NaOH, as a simple activator, and the other with NaOH and Na2SiO3, as a compound activator. The effects of the LDPE plastic bag waste and the activators on compressive strength, porosity, microstructure analysis, and efflorescence formation were correlated and discussed. The results showed that the replacement of sand with plastic waste at 50% and 100% proportionally reduced the compressive strength due to the increase in porosity caused by the waste, especially in the group of mortars with the simple activator, and included the formation of efflorescence. On the other hand, the compound activator increased the packing of the particles in the mortar, as observed in the images of the microstructure. This reduced porosity inhibited efflorescence and resulted in higher resistances that reached a maximum value of 22.68 MPa at 28 days in the group of 50% mortars with the compound activator. Therefore, the study showed that there is potential for the replacement of sand with plastic waste for the production of mortars, which can be considered a more sustainable building material.
Keywords: efflorescence; geopolymer; metakaolinite; plastic waste; sustainability